Primary and metastatic mucinous adenocarcinomas of the ovary: Evaluation of the diagnostic approach using tumor size and laterality - Khunamornpong S. (2014)
To evaluate the usefulness of the recently proposed algorithm (Seidman JD, Kurman RJ, Ronnett BM. Primary and metastatic mucinous adenocarcinomas in the ovaries: incidence in routine practice with a new approach to improve intraoperative diagnosis. Am J Surg Pathol 2003; 27: 985-93 [5]) that classifies mucinous adenocarcinomas of the ovary as primary when they were unilateral > or =10 cm and as metastatic when they were unilateral <10 cm or bilateral.